Synthesis and Antimicrobial Evaluation of Fluorinated Chalcones - Rama Rao, Nadendla (Asian Journal of Chemistry, 2010)
In the present paper some fluorinated chalcones were synthesized and were screened for their antibacterial activities. All the compounds exhibited antibacterial activity.